Physical crosslinking of lipase from Rhizomucor miehei immobilized on octyl agarose via coating with ionic polymers: Avoiding enzyme release from the support. (March 2017) - Fernandez-Lopez, Laura; Pedrero, Sara G.; Lopez-Carrobles, Nerea; Virgen-Ortíz, Jose J.; Gorines, Beatriz C.; Otero, Cristina; Fernandez-Lafuente, Roberto
Graphical abstract: Highlights: OC-RML releases enzyme to the medium at high T, in the presence of detergents or high concentrations of cosolvents. OC-RML-PEI-DS has a reduced release of enzyme to the medium under drastic conditions. OC-RML-PEI-DS is much more stable than OC-RML under several studied inactivation conditions. It is possible to recover OC support by washing under carefully selected conditions. Abstract: Lipase from Rhizomucor miehei (RML) was immobilized on octyl-agarose (OC) at different loadings. Using low enzyme loadings (1/7 of the maximum loading), the incubation of the enzyme with polyethylenimine (PEI) increased the resistance to enzyme desorption in the presence of Triton X-100. However, more than 10% of the enzyme activity could be released from the OC-RML-PEI. The same treatment using fully loaded biocatalyst reduced the enzyme desorption to less than 5%. Further treatment with dextran sulfate (DS) of the PEI treaded immobilized enzyme fully avoids the enzyme desorption even in presence of a Triton X-100 concentration higher than that required for the complete enzyme release from OC-RML. This treatment produced a high stabilization of OC-RML in thermal or organic solvent inactivations, reducing the enzyme release under these drastic conditions. Nevertheless, the support could be recovered by incubation under adequate conditions, and reused in several adsorption/desorption cycles. Thus, the strategy permitted to avoid enzyme desorption, very likely by physical intermolecular crosslinking improving enzyme stability, while still maintaining the reversibility of the immobilization.